Uji Aktivitas Antioksidan Ekstrak Metanol Biji Kesumba Keling (Bixa orellana L) - Souhoka, Fensia Analda; Hattu, Nikmans; Huliselan, Marsye (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2019)
Kesumba keling (Bixa orellana L) has been widely used as a natural dye on lips, hair, and cloth. The red pigment in kesumba keling seeds comes from a bixin and norbixin compound which have many conjugated double bonds, so it has the potential of antioxidants. This study aims to determine the antioxidant compound and an antioxidant activity of methanol extract of kesumba keling seeds. The moisture content of kesumba keling seeds is 78.74%. The powder of kesumba keling seeds was extracted using maceration method with 80% of methanol. Phytochemical test results of methanol extract positively contained flavonoid compound. An antioxidant activity test of methanol extract of kesumba keling seeds was carried out by determining DPPH free radical deterrent activity. The absorbance measurement were made using a UV-Vis spectrophotometer at a wavelength of 517 nm. Kesumba keling seeds extract has antioxidant activity which is indicated by IC50 value of 69.425 ppm, so it is classified as a strong antioxidant.